Socioeconomic Context as a Moderator in the Relationship between Body Mass Index and Depression in Europe. Issue 3 (24th November 2017) - Alvarez‐Galvez, Javier; Gomez‐Baya, Diego
Abstract : Background: Obesity and depression are two major health issues in contemporary societies. This study aims to address two fundamental questions: (1) what is the impact of macro‐level adverse socioeconomic circumstances on depression? and (2) how do macro‐level variations in the socioeconomic context affect the relationship between body mass index (BMI) and depression? Methods: Data from the 7th round of the European Social Survey were used, collected from a sample size of 37, 623 participants and aggregated around a total of 20 countries. A random intercept multilevel model was constructed to study the variations in the relationship between depression and BMI. The contextual effect of risk of poverty, unemployment rate, and gross domestic product per capita were studied at the country level. Results: First, both unemployment and poverty risk were found to be positively associated with depressive disorders. Second, the results show that a higher risk of poverty at the macro level may increase the effect of BMI on depression in European countries. Conclusion: The present study provides new evidence suggesting that the obesity–depression relationship will be, on average, stronger in countries with poor socioeconomic conditions. Therefore, adverse socioeconomic contextual conditions may increase depression associated with obesity.